Ukraine Systematic Country Diagnostic : Toward Sustainable Recovery and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2017)
Ukraine has tremendous potential that has not yet been reached. Ukraine is endowed with intelligent, energetic, and entrepreneurial people; extraordinary fertile land; considerable natural resources; and a geographic location at the crossroads of Europe and Asia. There is no reason why Ukraine, under the right conditions, should not be among the league of prosperous and successful nations. The circumstances today, however, are of course, still far from that ultimate target. Ukraine’s GDP per person in 2015 was $2,115, while the corresponding figure was $12,500 for Poland, around $9,000 for Turkey and Romania, and $9,800 for Malaysia, and $13,000 for Argentina. The flip side of the current circumstances is that if Ukraine is able to put in place the right conditions, it will experience a period of strong economic growth as it catches up and converges to the levels of income of more prosperous nations. This Systematic Country Diagnostic (SCD) for Ukraine is intended as an evidence based diagnostic of the constraints and priorities to reduce poverty and promote shared prosperity in a sustainable way. The SCD is intended as an evidence‐based and integrative analytical report, combining analysis of growth, inclusion, and sustainability. The SCD is not intended to be limited to expected areas of World Bank Group (WBG) engagement, but is instead intended to assess what the country itself should do to advance its growth, poverty reduction, and shared prosperity objectives in a sustainable way. This SCD is structured as follows. The next section covers the analysis of growth and sustainability. The third section covers the analysis of poverty and shared prosperity. The fourth section uses the analysis from the prior two sections to lay out the framework for the SCD, including the constraints and pathways to sustainable recovery and shared prosperity for Ukraine. The fifth, sixth, seventh, and eighth sections elaborate on the pathways to achieving sustainable recovery and shared prosperity in Ukraine.